Mirror mirror : the classic tale comes to life "spectacular" ([Place of publication not identified] Studio Canal Limited, 2012)
A classic fairy tale Snow White gets a modern makeover in the encahanting Mirror mirror in a kingdom far away an evil queen. Mirror mirror breathes fresh air into the classic story of Snow White.. A treat for all the family.
Keywords: Snow White (Tale) -- Drama -- Queens -- Drama -- Dwarfs (Folklore) -- Drama